Intraventricular Conduction Disturbances After Transcatheter Aortic Valve Implantation. Issue 1 (2020) - Lin, Shu-I; Miura, Mizuki; Puri, Rishi; Tagliari, Ana Paula; Lee, Francesco Maisano Ying-Hsian; Shirai, Shinichi; Taramasso, Maurizio
No abstract available